Impacts of springtime biomass burning in the northern Southeast Asia on marine organic aerosols over the Gulf of Tonkin, China. (June 2018) - Zheng, Lishan; Yang, Xiaoyang; Lai, Senchao; Ren, Hong; Yue, Siyao; Zhang, Yingyi; Huang, Xin; Gao, Yuanguan; Sun, Yele; Wang, Zifa; Fu, Pingqing
Abstract: Fine particles (PM2.5 ) samples, collected at Weizhou Island over the Gulf of Tonkin on a daytime and nighttime basis in the spring of 2015, were analyzed for primary and secondary organic tracers, together with organic carbon (OC), elemental carbon (EC), and stable carbon isotopic composition (δ 13 C) of total carbon (TC). Five organic compound classes, including saccharides, lignin/resin products, fatty acids, biogenic SOA tracers and phthalic acids, were quantified by gas chromatography/mass spectrometry (GC/MS). Levoglucosan was the most abundant organic species, indicating that the sampling site was under strong influence of biomass burning. Based on the tracer-based methods, the biomass-burning-derived fraction was estimated to be the dominant contributor to aerosol OC, accounting for 15.7% ± 11.1% and 22.2% ± 17.4% of OC in daytime and nighttime samples, respectively. In two episodes E1 and E2, organic aerosols characterized by elevated concentrations of levoglucosan as well as its isomers, sugar compounds, lignin products, high molecular weight (HMW) fatty acids and β -caryophyllinic acid, were attributed to the influence of intensive biomass burning in the northern Southeast Asia (SEA). However, the discrepancies in the ratios of levoglucosan to mannosan (L/M) and OC (L/OC) as well as the δ 13 C values suggest the type of biomass burning and the sources of organic aerosols in E1 and E2 were different. Hardwood and/or C4 plants were the major burning materials in E1, while burning of softwood and/or C3 plants played important role in E2. Furthermore, more complex sources and enhanced secondary contribution were found to play a part in organic aerosols in E2. This study highlights the significant influence of springtime biomass burning in the northern SEA to the organic molecular compositions of marine aerosols over the Gulf of Tonkin. Graphical abstract: Image 1 Highlights: Primary and secondary organic tracers were quantified in marine aerosols over the Gulf of Tonkin. Levoglucosan was the dominant organic species in the fine aerosols. Different sources and composition of organic aerosols were observed during different biomass-burning episodes. Abstract : Springtime biomass burning in the northern SEA significantly influenced the organic molecular compositions of marine aerosols over the Gulf of Tonkin.